2011
DOI: 10.1108/02686901211186108
|View full text |Cite
|
Sign up to set email alerts
|

Earnings management and board oversight: an international comparison

Abstract: Purpose -This paper attempts to investigate the relationships between the board of directors' characteristics and earnings management being a proxy of earnings quality in two separate countries, France and Canada. Specifically, it aims to investigate how certain contextual features affect differently earnings management behavior, and to reveal which factors are the most prominent incentives of management discretion in both cases. Design/methodology/approach -The paper uses a performance matched discretionary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 59 publications
1
30
0
5
Order By: Relevance
“…The study conducted by Jouber and Fakhfakh (2012) shows that some of the strong earnings factors are CEO stock ownership, independent monitoring and institutional investor's property in both the French and Canadian structures. On the other hand, Yang et al (2009) examine the external directors and institutional shareholders roles in limiting the earnings management activities on Malaysian companies.…”
Section: Earnings Management and Institutional Ownershipmentioning
confidence: 99%
“…The study conducted by Jouber and Fakhfakh (2012) shows that some of the strong earnings factors are CEO stock ownership, independent monitoring and institutional investor's property in both the French and Canadian structures. On the other hand, Yang et al (2009) examine the external directors and institutional shareholders roles in limiting the earnings management activities on Malaysian companies.…”
Section: Earnings Management and Institutional Ownershipmentioning
confidence: 99%
“…The separation of roles within the BOD will reduce agency problems and harmonize the interests of owners and management (Klein, 2002). It also supports the board's independence and limits the executive director's control of the board (Taktak and Mbarki, 2015;Jouber and Fakhfakh, 2012). Role duality is argued to be associated with high levels of earnings management (Cornett et al, 2009;Mohamad et al, 2012) because it provides greater freedom for executives to practice accounting discretion and manipulating financial reports (Saleh et al, 2005).…”
Section: Role Dualitymentioning
confidence: 99%
“…Since 1980s, researchers have attempted to develop models of discretionary accruals such as Healy (1985), DeAngelo (1986), and Jones model (1991) which developed in Dechow et al (1995). Accounting research then proceeded to explore the potential role of corporate governance in reducing earnings management practices (Abdul Rahman and Ali, 2006;Jouber and Fakhfakh, 2012;Mohamad et al, 2012;Xie et al, 2003).…”
Section: Previous Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…It mainly happens if the relationship between the agent and the principal is influenced due to some inadequacies, or if the corporate governance implementations are not availed. Many recent studies on earnings quality revealed that when managerial discretion occurs, the organization's real economic performance is lost (Jouber & Fakhfakh, 2011). In addition, many studied the factors and constraints that affect earnings management.…”
Section: Earnings Managementmentioning
confidence: 99%